2010
DOI: 10.1182/blood-2009-11-255182
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of PET scanning before and after reduced-intensity allogeneic stem cell transplantation for lymphoma

Abstract: Allogeneic stem cell transplantation (SCT)is an established therapy for patients with relapsed lymphoma, but the role of positron emission tomography (PET) scanning preallogeneic and postallogeneic SCT is uncertain. We investigated whether pretransplantation PET status predicted outcome after allogeneic SCT and whether PET surveillance after transplantation provided additional information compared with computed tomography (CT) scanning. Eighty consecutive patients with lymphoma who received a reduced-intensity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 21 publications
(25 reference statements)
3
45
0
Order By: Relevance
“…Although a positive PET/CT scan immediately before the high-dose chemotherapy does predict a lower likelihood of cure, at least 7%-56% of patients with a positive scan remain free of subsequent relapse in the studies that have been reported. [32][33][34][35][36][37] With no alternative reliably curative treatment available, it would not be prudent to abandon high-dose chemotherapy for these patients. Whether a strategy of turning to a different potentially non-cross-resistant chemotherapy regimen in another attempt to induce a negative PET/CT scan will lead to improved outcomes is untested.…”
Section: Monitoring For Evidence Of Relapse After Completion Of Plannmentioning
confidence: 99%
“…Although a positive PET/CT scan immediately before the high-dose chemotherapy does predict a lower likelihood of cure, at least 7%-56% of patients with a positive scan remain free of subsequent relapse in the studies that have been reported. [32][33][34][35][36][37] With no alternative reliably curative treatment available, it would not be prudent to abandon high-dose chemotherapy for these patients. Whether a strategy of turning to a different potentially non-cross-resistant chemotherapy regimen in another attempt to induce a negative PET/CT scan will lead to improved outcomes is untested.…”
Section: Monitoring For Evidence Of Relapse After Completion Of Plannmentioning
confidence: 99%
“…[1][2][3][4] However, the risk of progressive disease or relapse is considerably greater if the recipient is in partial remission at the time of transplantation or if mixed rather than complete chimerism develops when nonmyeloablative conditioning is used. [5][6][7][8] The goal of the current study was to identify a freshly isolated subset of donor T cells with potent antilymphoma activity that could promote complete chimerism without inducing severe graft-versus-host disease (GVHD) after allogeneic bone marrow transplantation (BMT) in mice.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, early interventions with therapeutic DLI directed by serial flurodeoxyglucose positron emission tomographic imaging are also linked with long-term disease control (Lambert et al, 2010). In these settings, directed delivery of pre-emptive or therapeutic DLI is associated with a low incidence of GVHD (Lambert et al, 2010;Thomson et al, 2010;Peggs et al, 2011).…”
mentioning
confidence: 99%